Pengembangan Aplikasi TUKKOT ASI Berbasis Budaya Batak Mambosuri Dalam Peningkatan Kesiapan Pemberian ASI Eksklusif Pada Ibu Hamil Trimester III: Development of the TUKKOT ASI Application Based on Batak Mambosuri Culture to Enhance Readiness for Exclusive Breastfeeding among Third-Trimester Pregnant Women - Nainggolan, Anna Waris; Silaban, Marta Armita; Simanjuntak, Parningotan; Simanullang, Cesy Marlianata; Siagian, Lastini (Amerta Nutrition, 2026)
Background: Exclusive breastfeeding rate in Indonesia was 68%, which were also lower than the targeted national 80%. One such cause is unpreparedness of pregnant women for breastfeeding. In Batak culture, the Moumbasuri method during pregnancy month seven is regarded as a social, spiritual and psychosocial intervention to support pregnant women, but has not been adequately utilised to reinforce breastfeeding preparation. This type of local wisdom can be incorporated into digital media for better readiness toward exclusive breastfeeding among third trimester pregnant mothers. Objective: To develop and evaluate the Technology for Optimal Readiness (TUKKOT) ASI application, grounded in Mambosuri culture, as an educational tool to enhance readiness for exclusive breastfeeding. Methods: The used Research and Development (R&D) model was based on the structure of Analysis, Design, Development, Implementation, and Evaluation (ADDIE). It was composed by needs analysis, content design, validation with specialists and implementation (40 pregnant women on the third trimester) and evaluated using Wilcox test. Outcomes: The analysis showed that 57.5% of participants had low knowledge, while 47.5% demonstrated good readiness. The application featuring home, Mambosuri, readiness, and profile sections received an expert feasibility score of 88.9%. After a one month period, a user satisfaction level of 90.8% was achieved. Significant improvements were demonstrated through statistical analysis in knowledge (p-value<0.001), family support (p-value<0.005), and readiness for breastfeeding (p-value<0.001). Conclusion: An effective increase in knowledge, family support, and breastfeeding preparedness among women in the third trimester of pregnancy was achieved through the use of the Mambosuri based TUKKOT ASI application. Embedding local wisdom in digital media is one strategic method to support the success of Indonesia’s exclusive breastfeeding program.